2016
DOI: 10.1200/jco.2015.65.3519
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin As Secondary Prevention in Patients With Colorectal Cancer: An Unselected Population-Based Study

Abstract: Aspirin use after the diagnosis of CRC is independently associated with improved CSS and OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 21 publications
2
68
3
Order By: Relevance
“…In fact, our results confirmed that SII is indeed superior to PLR, NLR and MLR. In addition, many studies have confirmed that non-steroidal anti-inflammatory drugs (NSAIDs) are associated with improved survival outcomes in patients with cancer, including esophageal cancer2526. The patients with ESCC who have a high SII maybe especially benefit from targeted anti-inflammatory with aspirin and non-steroidal anti-inflammatory drugs (NSAIDs).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, our results confirmed that SII is indeed superior to PLR, NLR and MLR. In addition, many studies have confirmed that non-steroidal anti-inflammatory drugs (NSAIDs) are associated with improved survival outcomes in patients with cancer, including esophageal cancer2526. The patients with ESCC who have a high SII maybe especially benefit from targeted anti-inflammatory with aspirin and non-steroidal anti-inflammatory drugs (NSAIDs).…”
Section: Discussionmentioning
confidence: 99%
“…Targeted agents that regulate inflammation and immunity may improve the prognosis of patients with immune-mediated diseases. Aspirin was demonstrated to be helpful in protecting patients with chronic hepatitis from HCC [30] and could also be effective as secondary prevention in patients with colorectal cancer [31]. Thymosin has shown antitumor effects via enhancement of the Th1 immune response [32].…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, there have been many studies on aspirin and its effectiveness in the treatment of colorectal cancer. In pre‐clinical studies, aspirin has been found to reduce the incidence of CRC and it is used as secondary prevention in patients with CRC . Aspirin can inhibit cell proliferation and pro‐apoptosis in several tumour‐derived cell lines, the mechanism of which is through the inhibition of the Wnt/β‐catenin pathway, vascular endothelial growth factor (EGFR) activation, NF‐κB and COX‐2 expression …”
Section: Introductionmentioning
confidence: 99%